1997
DOI: 10.1103/physrevb.56.15712
|View full text |Cite
|
Sign up to set email alerts
|

Electroabsorption spectroscopy of luminescent and nonluminescent π-conjugated polymers

Abstract: We have measured the quadratic electroabsorption ͑EA͒ spectrum of a variety of soluble luminescent and nonluminescent-conjugated polymer films in the spectral range of 1.5-4.5 eV. The luminescent polymers include MEH and DOO derivatives of poly͑phenylene-vinylene͒, poly͑phenylene ethylene͒, and polythiophene; the nonluminescent polymers include poly͑diethynyl silane͒ and monosubstituted polyacetylene. All EA spectra show a Stark shift of the low-lying odd-parity exciton (1B u) and imply the presence of phonon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
216
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(243 citation statements)
references
References 93 publications
22
216
3
Order By: Relevance
“…This feature is not observed in the EA spectra of DOO-PPV and other PPV derivatives containing only para-phenylene rings. 19,31 However, we have observed similar features in the EA spectra of distyrylbenzene derivatives where the central para-phenylene ring has been replaced by a meta-phenylene ring. 32 The EA spectrum is a weighted average of a number of phonons that couple to the electronic transition.…”
Section: Electronic Structure Of 13-ppvmentioning
confidence: 59%
See 2 more Smart Citations
“…This feature is not observed in the EA spectra of DOO-PPV and other PPV derivatives containing only para-phenylene rings. 19,31 However, we have observed similar features in the EA spectra of distyrylbenzene derivatives where the central para-phenylene ring has been replaced by a meta-phenylene ring. 32 The EA spectrum is a weighted average of a number of phonons that couple to the electronic transition.…”
Section: Electronic Structure Of 13-ppvmentioning
confidence: 59%
“…Comparison of the derivative absorption and EA spectra in Fig. 3 results in a maximum polarizability ⌬pϭ623 Å 3 at 2.9 eV, more than an order of magnitude less than Liess et al 19 calculated for several luminescent conjugated polymers ͑including substituted PPV derivatives͒. The polarizability of the lowest excited state of 1,3-PPV is only 50% larger than that of trans,trans'-distyrylbenzene (420 Å 3 ).…”
Section: Electronic Structure Of 13-ppvmentioning
confidence: 92%
See 1 more Smart Citation
“…This zeroth derivative contribution to the EA spectrum will also result in an apparent second derivative component, as the transfer of oscillator strength results in a small perturbation of the first derivative component which can be approximated by a second derivative in a Taylor-like expansion. Recently Liess et al 11 showed that a significant contribution to the second derivative component of the EA response of conjugated polymers can also arise from the distribution of conjugation lengths that exists in most conjugated polymer systems. They showed that the EA spectra in the region of the low-lying excitations for a wide range of conjugated polymers could be interpreted solely in terms of neutral excitations.…”
Section: T ϭD⌬␣ϩ 2 1ϫr ⌬R ͑1͒mentioning
confidence: 99%
“…Recently, Liess et al 11 modeled the EA spectra of a variety of conjugated polymers using a sum-over-states ͑SOS͒ approach incorporating three essential states and an asymmetric distribution of conjugation lengths. These three essential states are the ground state ͑the 1A g ), the lowest oddparity excited state ͑the 1B u ), and an even-parity state strongly coupled to the 1B u ͑the mA g ).…”
Section: Introductionmentioning
confidence: 99%